PENELITIAN JOINT SEALANT UNTUK SAMBUNGAN PERKERASAN BETON SEMEN - Leksminingsih Leksminingsih (Direktorat Bina Teknik Jalan dan Jembatan, 2009)
Joint sealant is used for concrete pavement joints. To fulfill joint sealant requirements, laboratory tests have been carried out except weathering test therefore for this purpose, experiments by simulation on concrete pavement is required in order to conform to all requirements for use in sealing joints in concrete pavements. Joint sealant is made of asphalt pen 60 added by elastomeric or platomeric materials which available in Indonesia. The mixture should be heated at high temperature with a minimum of 170Â°C. The results of laboratory tests of sealing compound, i.e. penetration, flow, bond, curing and durability were obtained. (ASTM 3405,2005). The research has found out joint sealant mixture which conforms to ASTM requirementsconsisting of asphalt pen 60 with 3,5% elastomer (natural rubber RSS1 type) and 8% plastomer (plastic). Specified joint sealant can be used for concrete pavement..observation. Field experiment of joint sealant was also performed in a road link of Tambun â€“ Cimuning, Bekasi.After three month observations, joint sealant showed no failure, or loose materials, but the application of other joint sealant as comparison reached failure measurement more than 80%. The important recommendation for joint sealant in application is surface preparation. Pavement surface should be clean and dry so that the sealant specimens will be more adhesive. Keywords : joint sealant. masterbatch rubberized bitumen.,elastomer. plastomer. concrete pavement